Laterborns Don't Give Up: The Effects of Birth Order on Earnings in Europe - Marco Bertoni; Giorgio Brunello (Institute for the Study of Labor (IZA), 2013)
While it is well known that birth order affects educational attainment, less is known about its effects on earnings. Using data from eleven European countries for males born between 1935 and 1956, we show that firstborns enjoy on average a 13.7 percent premium over laterborns in their wage at labour market entry. However, this advantage is short lived, and disappears by age 30, between 10 and 15 years after labour market entry. While firstborns start with a better match, partly because of their higher education, laterborns quickly catch up by switching earlier and more frequently to better paying jobs. We argue that a key factor driving our findings is that laterborns are more likely to engage in risky behaviours.
Keywords: D13; J12; J24; 330; birth order; earnings; risk aversion; Europe